PENGARUH PENGGUNAAN BUKU CERITA “AKU DAN LEMBONGAN” DALAM PEMBELAJARAN SUBTEMA LINGKUNGAN TEMPAT TINGGALKU TERHADAP MINAT BACA DAN HASIL BELAJAR SISWA KELAS IV SD - Ni Putu Widyasanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This study aimed to investigate the effect of the use of storybooks on reading interest and learning outcomes in fourth grade students of Elementary School XIII Buleleng District. Of the 157 students of the population, 64 students were designated as samples drawn by random sampling technique. Data collected by the reading interest questionnaire, while learning outcomes data collected by objective tests. Data analysis technique used in this research is Manova. The result of the research shows that: 1) There are differences of reading interest between students who are taught by accompanying by a story book and taught only using the 2013 Curriculum Book on learning Subtheme of My Neighborhood in fourth grade students of Elementary School XIII Buleleng District, 2) there is a difference in learning outcomes between students who were taught by accompanied by a story book and taught only using the 2013 Curriculum Book on learning Subtheme of My Neighborhood in fourth grade students of Elementary School XIII Buleleng District, 3) there are differences of simultaneous reading interest and learning outcomes between students who were taught accompanied by a story book and taught only using the 2013 Curriculum Book on learning Subtheme of My Neighborhood in fourth grade students of Elementary School XIII Buleleng District.Keywords: Storybook, Learning Outcomes, Reading Interest